1986
DOI: 10.1083/jcb.102.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Growth control in cultured 3T3 fibroblasts. V. Purification of an Mr 13,000 polypeptide responsible for growth inhibitory activity.

Abstract: Abstract. A growth regulatory factor, which reversibly inhibits DNA synthesis and proliferation of fibroblasts, has been isolated from medium conditioned by exposure to density-inhibited mouse 3T3 cells. This factor, termed FGR-s (13K), yielded a single polypeptide (Mr 13,000) when analyzed by SDS PAGE under both reducing and nonreducing conditions. The doseresponse curve of growth inhibition by FGR-s (13K) showed that 50% inhibition of 3T3 cell proliferation was achieved at a concentration of-3 ng/ml, corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Fifth, the potent mammaryderived growth inhibitory protein from bovine lactating (nongrowing) mammary glands reversibly suppresses cell multiplication and thymidine incorporation in a variety of epithelial cells (46). Sixth, the fibroblast growth regulator-soluble, a protein that is secreted by growth-inhibited NIH 3T3 cells at confluence, reversibly blocks DNA synthesis and cell replication at 0.1 nM in a variety of fibroblast lines (47,48). Collectively, these different systems support the present finding of a link between L-FABP and inhibition of cell multiplication.…”
supporting
confidence: 74%
“…Fifth, the potent mammaryderived growth inhibitory protein from bovine lactating (nongrowing) mammary glands reversibly suppresses cell multiplication and thymidine incorporation in a variety of epithelial cells (46). Sixth, the fibroblast growth regulator-soluble, a protein that is secreted by growth-inhibited NIH 3T3 cells at confluence, reversibly blocks DNA synthesis and cell replication at 0.1 nM in a variety of fibroblast lines (47,48). Collectively, these different systems support the present finding of a link between L-FABP and inhibition of cell multiplication.…”
supporting
confidence: 74%
“…Gap junctional coupling may exert an effect on cell proliferation by influencing the secretion of a soluble growth inhibitor. Several reports have described a growth-inhibitory effect offibroblast-conditioned medium on a variety of normal and tumor cell types (7,13,(24)(25)(26). In preliminary studies, we have found that conditioned medium from connexin 43-transfected C6 cells also inhibits the growth of several other tumor cell lines (22).…”
Section: Discussionmentioning
confidence: 99%
“…Several candidate molecules have been identified. For example, Swiss 3T3 cells secrete a molecule termed fibroblast growth regulator (FGR-s; Hsu and Wang, 1986), embryonic mouse fibroblast secrete an insulin-like growth factor binding protein (IGFBP-3;Blat et al, 1994) that is thought to inhibit their proliferation, while cultured human mammary cells secrete an inhibitor termed mammastatin (Ervin et al, 1989). Some potential inhibitors of cell proliferation are not particularly cell specific.…”
Section: Introductionmentioning
confidence: 97%